L10 Two novel mtor and PI3K/mTOR inhibitors induce autophagy and reduce the amount of aggregated mutant huntingtin in cell models of HD. (13th September 2016) - Singer, Elisabeth; Walter, Carolin; Hillmann, Petra; Fabbro, Doriano; Riess, Olaf; Nguyen, Huu P
Abstract : Background: The pathogenesis of HD is not entirely understood, but it is clear that the expression of the disease-causing mutant huntingtin protein leads to the disruption of a variety of cellular functions, which ultimately results in cell death. A hallmark of HD is the accumulation of intracellular inclusions of mHTT, the mHTT aggregates. Although the toxicity of mHTT aggregates is still debated, various studies have demonstrated that induction of autophagy, the major pathway for the degradation of mHTT aggregates, leads to increased cell viability. ATP- competitive mTOR inhibitors have been shown to be more efficient in induction of autophagy and reduction of protein aggregates than allosteric mTOR inhibitors, like Rapamycin. Aim: The ability of catalytic mTOR inhibitors to cross the blood-brain barrier, however, is limited and mTOR inhibition in brain is insufficient. Therefore two novel mTOR inhibitors were evaluated for their efficacy in mTOR inhibition in an HD context, by assessing their potential for inducing autophagy and reducing HTT levels. Methods: Expression levels of autophagic markers and well-studied mTOR targets were analysed by western blot analysis in STHdhQ7/Q7 and STHdhQ111/Q111 cells and brain samples from mice treated with both compounds. Cytotoxic effects were monitored in STHdh cells. For studying HTT levels HEK293T cells were transiently transfected with HTT- Exon 1- eGFP constructs with either 19 or 51 Q and analysed by fluorescent imaging and filter trap assay. Results: Treatment with both compounds led to decreased cytotoxicity in STHdh cells. The phosphorylation level of mTOR targets 4EBP1 and ribosomal protein S6 were found to be reduced, while LC3B – II levels increased in vitro and in vivo, indicating inhibition of mTOR activity and induction of autophagy. Furthermore reduction of aggregates was demonstrated upon treatment with both substances. Conclusion: Originally derived from cancer treatment, these second generation mTOR inhibitors show brain penetrance and effectiveness in cell models of HD, which suggests them as potentially relevant in treatment of neurodegenerative disorders.